2017
DOI: 10.1016/j.molstruc.2016.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Structural and energetic properties of haloacetonitrile – GeF4 complexes

Abstract: The 1:1 and 2:1 complexes of FCH 2 CN and ClCH 2 CN with GeF 4 have been investigated by M06/aug-cc-pVTZ calculations, low-temperature, thin-film IR spectroscopy, and an x-ray structure has been obtained for (FCH 2 CN) 2-GeF 4. Theoretical structures and binding energies for FCH 2 CN-GeF 4 and ClCH 2 CN-GeF 4 demonstrate that halogen substitution significantly weakens the Ge-N dative bonds. The Ge-N distances for the F-and Cl-complexes (2.447 and 2.407 Å, respectively) are about 0.2 Å longer than in CH 3 CN-Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…[87] Computations was carried out with the Gaussian 09 software. [76,77] [89][90][91] The molecular electrostatic potentials (MEPs) of the isolated monomers were designated on the electron density isosurfaces of 1 = 0.001 a.u.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…[87] Computations was carried out with the Gaussian 09 software. [76,77] [89][90][91] The molecular electrostatic potentials (MEPs) of the isolated monomers were designated on the electron density isosurfaces of 1 = 0.001 a.u.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The two NC � CFH 2 units are cis to one another in AYURET [76] in what might be deemed equatorial locations. As such they each occupy a position directly opposite an equatorial F atom, a so-called σ-hole along the F-Ge axis.…”
Section: Introductionmentioning
confidence: 99%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%
“…Computations are vital for characterizing gas‐phase systems and providing direct insight into the mechanism for medium‐induced structural change [ 181,213,393 ] and to enable them to identify promising targets and focus their experimental efforts. [ 181,394,395 ] Following up on their initial work on group IV halides (MX 4 : M = Ti, Si, Ge; X = F, Cl), [ 211,298,310 ] they are exploring the nitrile and imine complexes of the monoalkyl analogs (MX 3 R) of these acids.…”
Section: Overview Of Mercury Faculty Research Effortsmentioning
confidence: 99%
“…Subsequent studies of nitrogen‐donor‐MX 4 complexes (M=Si, Ge, Ti; X=F, Cl) [ 23–25 ] revealed some indication of condensed‐phase structural changes, but overall, those were much less dramatic than the observations noted above for the B‐N systems. One striking example was CH 3 CN–SiF 4 , for which a theory predicted a long gas‐phase Si‐N distance of about 3.0 Å that would shorten by over 1.0 Å in low‐dielectric media (ε=5).…”
Section: Introductionmentioning
confidence: 99%